Interaction-induced topological phase transition and Majorana edge states in low-dimensional orbital-selective Mott insulators - J. Herbrych (Nature Portfolio, 2021)
Superconductivity induced on a topological insulator’s surface may realize Majorana modes. Here, Herbrych et al. predict that a large Coulomb interaction helps develop a spiral spin order, which is a topological state at the edge of a canonical superconductor with orbital degrees of freedom.